What does emergency remote education tell us about home-schooling? - Kaya, Vildan Donmuş; Eroğlu, Mehmet (Gürhan DURAK, 2021)
The study aims to examine parents' opinions about Emergency Remote Education (ERE) during the pandemic and the feasibility of home-schooling in Turkey. The study uses a causal-comparative model. 654 parents took part in the study. ERE for Home-schooling Questionnaire developed by researchers is used to collect the data. Descriptive statistics, independent samples t-test, and ANOVA tests are used to analyse the data. The results of the study show that ERE during the pandemic is not effective enough. However, having someone at home to support the education of children can make ERE more effective. Parents have partial health anxiety about face-to-face education. Although parents have partially positive opinions about the feasibility of home-schooling, they also emphasize the need for support for home-schooling. As the parents' education level increases, both the challenges of home-schooling and the need for support for home-schooling decrease. Parents with low income have higher health anxiety than those with high income, and parents with low income need more support for home-schooling than those with high income. Parents who support their children's learning find ERE more effective and they find home-schooling more feasible. Parents who do not support their children's learning at home need more support for home-schooling. To practice home-schooling successfully, parents must have high level of education and must support their children's learning at home. Besides, institutions and organizations support parents for home-schooling.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar